Ebüssuud’un fıkhi meseleleri çözümündeki metodu - Fidan, Yılmaz (My University, 2007)
EBÜSSUÛD’UN FIKHÎ MESELELERĐ ÇÖZÜMÜDEKĐ METODU Bu çalısma ile Osmanlı fakihi Seyhülislâm Ebüssuûd’un fıkhî meseleleri çözümündeki metodu tespit edilmistir. O Đslâm hukuk mezheplerinden Hanefî okulunun yetistirdiği müctehid imamların görüslerine ve terimlerine bağlı kalmıstır. Genel olarak onların genis usul anlayısları Ebüssuûd tarafından sürdürülmüstür. Ebüssuûd, naklî metod, aklî metod, tercih metodu, ictihad metodu, maslahat metodu ve kolaylık metodunı uygulamıstır. Fetvalarında devlet sorumluluğu ve vicdânî sorumluluk tasıdığı gözlemlenmistir.

EBÜSSUÛD’S METHOD OF SOLUTION FOR FIQH PROBLEMS With the help of this study; it has been designated the method of sheiku’l-islâm Ebüssuûd’s in which he found solution to fiqh problems. Ebüssuûd is a mujtahid mufti of Ottoman state. He was committed himself to the rules and usages of mujtahid imams who had been trained by Hanafî school that was one of the Đslamic law madhhabs. Generally, Ebüssuûd practiced naqlî method, aqlî method, tercih method, ijtihad method, maslaha method and easiness method every time. It was seen In Ebüssuûd’s fatwas that he had had a govermental responsibility and his own conscience.
Keywords: İslam Hukuku